The Epistolary Moment : the Poetics of the Eighteenth-Century Verse Epistle. - Dowling, William C. (Princeton legacy library., 2014)
The eighteenth-century verse epistle, argues William Dowling, was an attempt to solve in literary terms the dilemma of solipsism as raised by Locke and Hume. The focus of The Epistolary Moment is on internal audience in poetry--the audience ""inside"" the poem, created by its discourse and belonging to its world--as this divides in epistolary poetry into a double or simultaneous register of address: the audience directly addressed by the letter-writer, and an epistolary audience listening in on the exchange from a point external to the discourse of the speaker but internal to the discourse